Unmasking the Difficulty of Listening to Talkers With Masks: lessons from the COVID-19 pandemic. (March 2021) - Giovanelli, Elena; Valzolgher, Chiara; Gessa, Elena; Todeschini, Michela; Pavani, Francesco
Interactions with talkers wearing face masks have become part of our daily routine since the beginning of the COVID-19 pandemic. Using an on-line experiment resembling a video conference, we examined the impact of face masks on speech comprehension. Typical-hearing listeners performed a speech-in-noise task while seeing talkers with visible lips, talkers wearing a surgical mask, or just the name of the talker displayed on screen. The target voice was masked by concurrent distracting talkers. We measured performance, confidence and listening effort scores, as well as meta-cognitive monitoring (the ability to adapt self-judgments to actual performance). Hiding the talkers behind a screen or concealing their lips via a face mask led to lower performance, lower confidence scores, and increased perceived effort. Moreover, meta-cognitive monitoring was worse when listening in these conditions compared with listening to an unmasked talker. These findings have implications on everyday communication for typical-hearing individuals and for hearing-impaired populations.